1996
DOI: 10.1093/hmg/5.12.1963
|View full text |Cite
|
Sign up to set email alerts
|

The sarcoglycan complex in the six autosomal recessive limb-girdle muscular dystrophies

Abstract: To enhance our understanding of the autosomal recessive limb-girdle muscular dystrophy (LGMD), patients from six genetically distinct forms (LGMD2A to LGMD2F) were studied with antibodies directed against four sarcoglycan subunits (alpha-, beta-, gamma-, delta-SG), dystrophin, beta-dystroglycan (beta-DG) and merosin. All patients with LGMD2A and 2B had a mild clinical course while those with a primary sarcoglycan mutation (LGMD2C to 2F) had a range of clinical severity. Dystrophin and merosin immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
6

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 35 publications
5
94
0
6
Order By: Relevance
“…Based on the above findings, we have suggested that α, and δ subunits of sarcoglycan might be more closely associated, whilst γ-SG might interact more directly with dystrophin. 12 Here we report two additional SGpathy patients with a 'DMD-like presentation' which gives further support to our previous study. In addition, one of them illustrates the potential risk of misdiagnosis in cases with a patchy pattern of dystrophin by means of IF methodology.…”
Section: Introductionsupporting
confidence: 90%
“…Based on the above findings, we have suggested that α, and δ subunits of sarcoglycan might be more closely associated, whilst γ-SG might interact more directly with dystrophin. 12 Here we report two additional SGpathy patients with a 'DMD-like presentation' which gives further support to our previous study. In addition, one of them illustrates the potential risk of misdiagnosis in cases with a patchy pattern of dystrophin by means of IF methodology.…”
Section: Introductionsupporting
confidence: 90%
“…In most muscle biopsies from patients with a primary sarcoglycanopathy, the primary loss or deficiency of any one of the four SG, ß-SG and d-SG in particular, leads to a secondary deficiency of the whole subcomplex ( Figure 3) (3,4,26,36,37). However, exceptions may occur, such as the deficiency of g-SG with a partial preservation of the other three SG in LGMD2C (37) or the partial deficiency of only a-SG with the retention of the other three in LGMD2D (36,38).…”
Section: Sarcoglycanopathiesmentioning
confidence: 99%
“…However, exceptions may occur, such as the deficiency of g-SG with a partial preservation of the other three SG in LGMD2C (37) or the partial deficiency of only a-SG with the retention of the other three in LGMD2D (36,38). The observation of a complete deficiency of one SG with partial deficiency of the others may help to indicate which gene should be first screened for mutations.…”
Section: Sarcoglycanopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine histological and histochemical analysis include staining for hematoxylin and eosin (H&E), modified Gomori trichrome, SDH, NADH, acid phosphatases, and ATPase at pH 9.4 and 4.3 15 Proteins analysis were performed through immunofluorescence (IF) and Western blot (WB) methodologies, as previously described. 16,17 The following antibodies were used: dystrophin, 18 sarcoglycans a, b, g and d, 19 calpain-3, 20 , dysferlin 21 and telethonin. 22 Microsatellite marker analysis DNA was isolated from blood by standard methods.…”
Section: Complementary Examinationsmentioning
confidence: 99%